Applanation Tonometry for Assessment of Left Ventricular Systolic Load - Rene Mileva-Popova; Nina Belova (Journal of Biomedical & Clinical Research)
Vascular-ventricular coupling is a major determinant of left ventricular load. The aim of our study was to assess non- invasively left ventricular load and its dependency on central hemodynamics. Sixty-five healthy and gender-matched individuals were divided in two groups according to their age: 20y/o and 50y/o. Applanation tonometry was performed using the Sphygmocor device. Central pressures and pulse wave analysis indices were computed. Central systolic (120±3 vs. 98±2 mm Hg) and pulse pressures (43±3 vs. 29±1 mm Hg) as well as the augmentation index (AIx75) (23±3 vs. 6±2%) were significantly higher in the 50y/o group (p